2020
DOI: 10.3389/fncel.2020.610342
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Changes of Corneal Nerves and Their Contribution to Peripheral and Central Sensory Abnormalities

Abstract: The cornea is the most densely innervated and sensitive tissue in the body. The cornea is exclusively innervated by C- and A-delta fibers, including mechano-nociceptors that are triggered by noxious mechanical stimulation, polymodal nociceptors that are excited by mechanical, chemical, and thermal stimuli, and cold thermoreceptors that are activated by cooling. Noxious stimulations activate corneal nociceptors whose cell bodies are located in the trigeminal ganglion (TG) and project central axons to the trigem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 156 publications
2
58
0
Order By: Relevance
“…Neuropeptides released by afferent nerve terminals function as both neurotransmitters and neuromodulators that lead to pain sensation [80][81][82] or neurogenic inflammatory responses [3,5,6]. The representative neuropeptides known to modulate immune reactions in response to external stimuli (mechanical, cold, and chemical stimuli; inflammatory mediators; damage-associated molecular patterns; and pathogen-associated molecular patterns) include SP, CGRP, VIP, and NPY [82][83][84][85][86][87].…”
Section: Representative Neuropeptides and Their Receptorsmentioning
confidence: 99%
“…Neuropeptides released by afferent nerve terminals function as both neurotransmitters and neuromodulators that lead to pain sensation [80][81][82] or neurogenic inflammatory responses [3,5,6]. The representative neuropeptides known to modulate immune reactions in response to external stimuli (mechanical, cold, and chemical stimuli; inflammatory mediators; damage-associated molecular patterns; and pathogen-associated molecular patterns) include SP, CGRP, VIP, and NPY [82][83][84][85][86][87].…”
Section: Representative Neuropeptides and Their Receptorsmentioning
confidence: 99%
“…Such phenomena have been largely described in the cornea [46] and are probably highly involved in sensitive corneas. Many morphological and functional changes of corneal nerve terminals were observed in DED patients, as well as peripheral and central neuroimmune interactions in the development of corneal hypersensitivity or cellular and molecular changes of corneal neurons [47,48]. These results should inspire research on sensitive skin.…”
Section: Lessons From the Bowel And The Eyesmentioning
confidence: 99%
“…Peripheral and central sensitization to pain and itch are possible in sensitive skin, sensitive eyes and irritable bowel syndrome [47]. Hence, the analysis of cerebral responses to cutaneous provocation tests in self-perceived sensitive and non-sensitive skin subjects using functional magnetic resonance imaging (fMRI) [49] showed that cerebral activity was significantly increased in the sensitive skin group.…”
Section: Lessons From the Bowel And The Eyesmentioning
confidence: 99%
“…As encompassed in this definition, recent studies have focused on the role of neurosensory abnormalities in the pathophysiology and semiology of DED [1,[7][8][9]. Indeed, reduced tear secretion and/or tear film instability lead to inflammation and peripheral nerve damage, triggering sensitization and abnormal activity in corneal nerves, evoking painful symptoms of dry eye associated with dryness, itching, and foreign body sensation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, some patients can present asymptomatic ocular surface alterations, and conversely, they can be highly symptomatic without obvious signs of ocular surface damage (i.e.,"pain without stain") [9,11,12]. In the second case, patients present with complaints of burning, stinging, eye-ache, photophobia, or severe eye pain without significant findings on slit-lamp examination [8,13]. The concept of "neuropathic corneal pain" (NCP), increasingly investigated in the past 20 years in clinical research [4,14], has been suggested to play a central role in those cases.…”
Section: Introductionmentioning
confidence: 99%